THE IMPACT OF FIRM CHARACTERISTICS ON ACCRUALS AND REAL EARNINGS MANGEMENT OF LISTED MANUFACTURING FIRMS IN NIGERIA - Aisha Chado Muhammad (Gusau Journal of Accounting and Finance, 2024)
The concerns about earnings management arose after the fall of many multinational companies. Extant literature has shown accruals and real earnings management techniques as dual ways of manipulating earnings. However, prior literatures have dwelled on AEM making it vast and creating a literature gap for REM with unanswered questions. This study examined the effect of firm characteristics on both and AEM was measured using the extended jones model by Yoon, Miller & Jirapon (2006) model while REM was measured by the Rowchowdhury (2006) model. The research sample was 40 firms drawn from listed manufacturing firms on the Nigerian Exchange Group (NGX) for the period 2007 to 2021. The ex post factor research design was used to determine the relationship between the dependent variable (Earnings management proxy by accruals earnings management and real earnings management), the independent variables (firm characteristics proxy by firm size, firms’ growth, firms’ profitability and audit quality) and the tradeoff between AEM and REM. The study used the multiple linear regressions as a tool of analysis. The results indicated; firm size has a consistent negative impact on both AEM and REM, with statistically significant results indicating that larger firms may face unique challenges related to financial reporting quality. Return on assets (ROA), have negative relationship with both AEM and REM which indicates Manager’s aggressive behavior to meet the benchmark has a significant positive association with both AEM and REM. Audit quality was also found to have a positive effect for both AEM and REM (0.0081 and 0.0008) which shows that the choice of audit firm affects both AEM and REM. Moreover, the results indicate that highly leveraged firms engage more in real earnings management than the accruals earnings management. The study concludes that firm growth measured by leverage has a significant positive impact on REM and higher this could be because managers decrease AEM because of strict audits and pressure of debt covenant. The perhaps increased REM knowing that detecting REM is more difficult than AEM, hence manipulated real activities with the purpose of observing finance obligations. Therefore, this study recommends heightened oversight and transparency, particularly in the context of real earnings management; regulators can work towards curbing detrimental practices that impact firm value.